If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(30 + s) = 4(s + 1s) (30 * 3 + s * 3) = 4(s + 1s) (90 + 3s) = 4(s + 1s) Combine like terms: s + 1s = 2s 90 + 3s = 4(2s) Remove parenthesis around (2s) 90 + 3s = 4 * 2s Multiply 4 * 2 90 + 3s = 8s Solving 90 + 3s = 8s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-8s' to each side of the equation. 90 + 3s + -8s = 8s + -8s Combine like terms: 3s + -8s = -5s 90 + -5s = 8s + -8s Combine like terms: 8s + -8s = 0 90 + -5s = 0 Add '-90' to each side of the equation. 90 + -90 + -5s = 0 + -90 Combine like terms: 90 + -90 = 0 0 + -5s = 0 + -90 -5s = 0 + -90 Combine like terms: 0 + -90 = -90 -5s = -90 Divide each side by '-5'. s = 18 Simplifying s = 18
| 13x-1=x+27 | | 5/3x:3/1 | | -9(x+3)+4x+5=6x+12 | | 8(31.25+-0.5y)+4y=250 | | 3(30+s)=4(s+1a) | | 2w+6=30 | | 2m+1=6m+2 | | 8(31.25+-0.5)+4y=250 | | x^4+6x^2+2x=0 | | 21m+36=3m | | 14x-21=49 | | (1/6x-5)-(6/5-6x) | | 8(x-9)=12 | | -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) |